Analogising Art Practice as Gameplay: A Dialogic Integration of Videogames as a Pluralistic Approach to Painting - See, Harrison W. (Art/Research International, 2026)
While video games are undeniably informed by the cultural and artistic traditions that precede them, this article outlines how video games can inform contemporary painting by discussing how a practice-led integration of video games that analogises art practice as gameplay can facilitate a pluralistic approach to storytelling. The story explored here was informed by my reflections on prior encounters of cross-cultural collaboration as informed by a dialogic approach to difference. Further, through a dialogic perspective that challenges oppositional thinking, the material and digital are positioned together at an intersection explored through painting-led dialogue. The article explores how integration and intersection are effective sources of creativity and a practical approach to challenging a practitioner’s familiar ways of thinking and making. I aim to encourage other practitioners to critically reflect on their influences to explore their own unique integrations.